Immunological Approaches Towards Cancer and Inflammation: A Cross Talk - Qu, Xinglong; Tang, Ying; Hua, Shucheng (Frontiers in Immunology, 2018)
The inflammation is the protective response of the body against various harmful stimuli, however, the aberrant and inappropriate activation tends to become harmful. The acute inflammatory response tends to resolved once the offending agent is subside but this acute response becomes chronic in nature when the body is unable to successfully neutralized the noxious stimuli. This chronic inflammatory microenvironment is associated with the release of various pro-inflammatory and oncogenic mediators such as nitric oxide (NO), cytokines (IL-1β, IL-2, IL-6 and TNF-α), growth factor and chemokines. These mediators make the inflammatory microenvironment more vulnerable towards tumorigenesis. The pro-inflammatory mediators released during the chronic inflammation tends to induce several molecular signaling cascades such as NF-κB, MAPKinase, Nrf2, Pi3K, JAK/STAT, Wnt/B-catenin, and CREB. The immune system and its components have a pleiotropic effect on inflammation and cancer progression. Immune components such as T cells, NK cells, macrophages, and neutrophils either inhibit or enhance tumor initiation depending upon the type of tumor and immune cells involved. Tumor-associated macrophages (TAMs) and tumor-associated neutrophils (TANs) are pro-tumorigenic cells highly prevalent in inflammation-mediated tumors. Similarly, presence of T regulatory (Treg) cells in an inflammatory and tumor setting suppresses the immune system, thus paving the way for oncogenesis. However, Treg cells also inhibit autoimmune inflammation. In contrast, cytotoxic T cells and T helper cells confer anti-tumor immunity and are associated with better prognosis in patients with cancer. Cytotoxic T cells inflict a direct cytotoxic effect on cells expressing oncogenic markers. Currently, several anti-inflammatory and anti-tumor therapies are under trials in which these immune cells are exploited. Adoptive cell transfer (ACT) comprised of tumor infiltrating lymphocytes (TILs) has been tried for the treatment of tumors after their ex vivo expansion. Mediators released by cells in a tumorigenic and inflammatory microenvironment cross talk with nearby cells, either promoting or inhibiting inflammation and cancer. Recently, several cytokine-based therapies are either being developed or are under trial to treat such types of manifestations. Monoclonal antibodies directed against TNF-α, VEGF, and IL-6 has shown promising results to ameliorate inflammation and cancer, while direct administration of IL-2 has been shown to cause tumor regression.